STUDI TINGKAT KERUSAKAN BIBIT MAHONI (Swietenia mahagoni) YANG DISEBABKAN OLEH SERANGGA DI PERSEMAIAN - Jabar Ali Dika; Basir Basir; Normela Rachmawati (Jurnal Sylva Scienteae, 2020)
This study aims to measure the frequency and intensity of insect attacks on mahogany seedlings (Swietenia mahagoni), also determine the level of damage that was caused by insect that attack mahogany seeds (S. mahagoni). Data used in this research is primary data and secondary data. Primary data is obtained through observations by making direct by grouping the level of insect attacks, secondary data is carried out by recording and measuring data to the agencies that was related to the environmental factors of the research location such as climate, humidity and temperature in the nursery. The results of the data shows that the frequency of insect attacks is about 78.6% and the frequency of leaf spot disease (leaf spot) is about 16%, while the overall attack of the frequency rate is about 94.6%, then the intensity of attacks on healthy seedlings is about 27, 317 seedlings were slightly damaged, 146 moderately damaged seeds, 1 seeds were severely damaged and 9 seedlings died with an intensity of attack of 32.4%, the damage rate that was caused by the insect and also leaf spot that attack mahogany seedlings (S. mahagoni) fall into the category of moderate damage. Based on the results of this study, insects and diseases that attack mahogany seedlings (S. mahagoni) in the nursery of The Centre of Watershed Management and Barito Protected Forests (BPDASHL) were green grasshopper insects (Oxya chinensis), stem borer insects (Xylosandrus sp.), Walang sangit insects (Leptocorisa acuta) and leaf spot diseases (leaf spot). Plant control is needed such as giving pesticides, natural enemies, from a kind of parasitoid wasp that attacks larvae Xylosandrus, and uses fungicides or wood vinegar.Keywords: Insects, Mahogany, Intensity of attacks, Level of damage